Systematic review and network meta-analysis of approved medicines for the treatment of idiopathic pulmonary fibrosis - Skandamis, Aristeidis (J Drug Assess, 2019)
Background: Clinical practice guidelines for the treatment of idiopathic pulmonary fibrosis (IPF) currently recommend pirfenidone and nintedanib. However, there is a lack of evidence from head-to-head comparisons. Objectives: To perform a systematic review and network meta-analysis (NMA) to access the efficacy and tolerability of two new treatments for IPF, pirfenidone and nintedanib. Methods: Randomized controlled trials (RCTs) selection (CENTRAL, MEDLINE, Embase), data extraction, risk of bias analysis, and GRADE assessment were carried out by two authors separately. Direct estimates were calculated using standard pairwise meta-analysis. A Bayesian mixed treatment comparison approach for NMA estimates, with 95% confidence intervals (CI), was used to compare the treatments, calculating odds ratios (OR) and number needed to treat (NNTB) or harm (NNTH). Results: The NMA on 10 randomized controlled trials showed that each drug had a positive effect on percentage of forced vital capacity (FVC) decline ≥ 10% (pirfenidone OR = 0.54 [95% CI = 0.37–0.80], NNTB = 9 [95% CI = 7–22]; nintedanib OR = 0.59 [95% CI = 0.41–0.84], NNTB = 9 [95% CI = 6–23]), but no significant differences were noted when comparing pirfenidone and nintedanib with respect to acute exacerbations, mortality, and serious adverse events (FVC decline OR = 0.91 [95% CI = 0.45–2.03]) or dropouts (OR = 0.75 [95% CI = 0.33–1.27]). Nintedanib showed an effect on dropouts, OR = 1.61 (1.13–2.28) and NNTH = 14 (8–61). Conclusions: Based on RCTs of 12 month duration in patients with IPF, a positive effect on FVC decline was noted for both treatments and on dropouts for nintedanib, but no significant differences were noted between treatments.